GTOC11: Methods and results from the team of Harbin Institute of Technology. (January 2023) - Zhang, Haiyang; Ma, Huidong; Yang, Lie; Lin, Xin; Xu, Longwei; Xia, Cunyan; Li, Jian; Li, Dai; Huo, Mingying; Zhang, Gang
Abstract: This paper presents the methods and the results submitted by the team of Harbin Institute of Technology in the 11th Global Trajectory Optimization Competition (GTOC11). The mission of GTOC11 is to design the Mother Ship trajectories to execute asteroid flybys selected from over 83000 candidates, and then transfer these asteroids to 12 stations to build the "Dyson Ring" while maximizing the total performance index. The building mission is completed by five steps: "Dyson Ring" orbit selection, database creation, Mother Ship trajectory design, building station construction strategy, and asteroid transfer trajectory optimization. The database creation is mainly used to fast estimate the transfer time for the asteroid low-thrust trajectory, and it plays an essential role in the whole mission. Finally, the building of the "Dyson Ring" is realized within the given period. The final index of the submitted result is 5208.3463, which ranked seventh in GTOC11. Highlights: To reduce computation burden for database, some nominal orbits are created to estimate transfer time. The flyby sequence of asteroids is obtained by the heuristic algorithm. The Bezier shape-based method is used as the initial guess for low thrust trajectory optimization. To make the asteroids reach the building station simultaneously, an inverse rendezvous method is proposed.